Artificial intelligence and the future of evaluation education: Possibilities and prototypes - Tilton, Zach; LaVelle, John M.; Ford, Tian; Montenegro, Maria (New Directions for Evaluation, 2023)
Advancements in Artificial Intelligence (AI) signal a paradigmatic shift with the potential for transforming many various aspects of society, including evaluation education, with implications for subsequent evaluation practice. This article explores the potential implications of AI for evaluator and evaluation education. Specifically, the article discusses key issues in evaluation education including equitable language access to evaluation education, navigating program, social science, and evaluation theory, understanding evaluation theorists and their philosophies, and case studies and simulations. The paper then considers how chatbots might address these issues, and documents efforts to prototype chatbots for three use cases in evaluation education, including a guidance counselor, teaching assistant, and mentor chatbot for young and emerging evaluations or anyone who wants to use it. The paper concludes with ruminations on additional research and activities on evaluation education topics such as how to best integrate evaluation literacy training into existing programs, making strategic linkages for practitioners, and evaluation educators.
<AI Smry>: Key issues in evaluation education including equitable language access to evaluation education, navigating program, social science, and evaluation theory, understanding evaluation theorists and their philosophies, and case studies and simulations are discussed. <标题>: 人工智能与评估教育的未来：可能性与原型 Read_Status: New Read_Status_Date: 2026-01-26T11:33:38.512Z
Keywords: /unread

Artificial intelligence and the future of evaluation education: Possibilities and prototypes - Tilton, Zach; LaVelle, John M.; Ford, Tian; Montenegro, Maria (New Directions for Evaluation, 2023)
Advancements in Artificial Intelligence (AI) signal a paradigmatic shift with the potential for transforming many various aspects of society, including evaluation education, with implications for subsequent evaluation practice. This article explores the potential implications of AI for evaluator and evaluation education. Specifically, the article discusses key issues in evaluation education including equitable language access to evaluation education, navigating program, social science, and evaluation theory, understanding evaluation theorists and their philosophies, and case studies and simulations. The paper then considers how chatbots might address these issues, and documents efforts to prototype chatbots for three use cases in evaluation education, including a guidance counselor, teaching assistant, and mentor chatbot for young and emerging evaluations or anyone who wants to use it. The paper concludes with ruminations on additional research and activities on evaluation education topics such as how to best integrate evaluation literacy training into existing programs, making strategic linkages for practitioners, and evaluation educators.
<标题>: 人工智能与评估教育的未来：可能性与原型 <AI Smry>: Key issues in evaluation education including equitable language access to evaluation education, navigating program, social science, and evaluation theory, understanding evaluation theorists and their philosophies, and case studies and simulations are discussed. Read_Status: New Read_Status_Date: 2026-01-26T11:33:31.077Z